Web Test Automation Framework - Amaro Gonzaga Martins da Silva (2013)
Software quality has become one of the most important differentiating factors in the software development industry. In order to deliver products with higher quality, strategies for test automation are being adopted. However, traditional test automation requires specific technical skills and if not well planned and implemented, it may end up being too complex and expensive to maintain. So the challenge is to use/develop test automation techniques that are efficient even in contexts of continuous evolving systems. This work presents a new scalable and flexible test automation framework for web based applications, based on the keyword-driven approach. Web Test Automation Framework provides a platform for the execution, implementation and management of system, integration and acceptance tests.